Spin transport in the frustrated anisotropic two-dimensional ferromagnet in the square lattice. (August 2016) - Lima, L.S.
Abstract: We use the SU(3) Schwinger boson formalism together with the Kubo theory of the linear response to study the spin transport in the two-dimensional S =1 frustrated anisotropic Heisenberg ferromagnet in a square lattice with easy-plane single-ion anisotropy and considering the second-neighbor interaction in the diagonal and the third-neighbor interaction ( J 1 – J 2 – J 3 model). The AC spin conductivity σ reg ( ω ) is determined for several values of the critical single-ion parameter D, and the frustration parameters J 2 and J 3 . We have calculated the dynamic structure factor too, S ( q →, ω ), for this model and obtained a behaviour exponentially decreasing for the damping Γ q with the decreasing of q = | q → | towards q → 0 . Abstract : Highlights: We study the spin transport of the model at T =0 with objective to verify the influence of the parameters of frustration η and λ in the spin conductivity. We consider the anisotropy parameter Δ = 1 → The phase diagram of the model presents a quantum phase transition in the points η 1 C and η 2 C → These points have an influence in the height of the spin conductivity σ reg ( ω ) → We calculate the dynamic structure factor S ( q, ω ) for different values of wave vector q . The parameters of frustration generate a bit influence on the spin conductivity and in the S ( q, ω ) .